Volitional and forced running ability in mice lacking intact primary motor cortex - Abo, Ryusei; Ishikawa, Mei; Shinohara, Rio; Michikawa, Takayuki; Imayoshi, Itaru (Frontiers in Neural Circuits, 2025)
The coordination of various brain regions achieves both volitional and forced motor control, but the role of the primary motor cortex in proficient running motor control remains unclear. This study trained mice to run at high performance (>10,000 rotations per day or >2,700 rotations per hour) using a running wheel, and then assessed the effects of the removal of bilateral cortical areas including the primary motor cortex on volitional (self-initiated) and forced (externally driven) running locomotion. The control sham-operated group revealed a quick recovery of volitional running, reaching half of the maximum daily rotation in 3.9 ± 2.6 days (n = 10). In contrast, the cortical injury group took a significantly longer period (7.0 ± 3.3 days, n = 15, p < 0.05) to reach half of the maximum volitional daily rotation, but recovered to preoperative levels in about two weeks. Furthermore, even 3 days after surgery to remove cortical regions, the running time on a treadmill moving at 35.3 cm/s, which is difficult for naïve mice to run on, was not significantly different from that in the sham-operated group. These results suggest that the intact primary motor cortex is not necessarily required to execute trained fast-running locomotion, but rather contributes to the spontaneity of running in mice.